Inflammation‐driven glial alterations in the cuprizone mouse model probed with diffusion‐weighted magnetic resonance spectroscopy at 11.7 T. (21st January 2021) - Genovese, Guglielmo; Palombo, Marco; Santin, Mathieu D.; Valette, Julien; Ligneul, Clémence; Aigrot, Marie‐Stéphane; Abdoulkader, Nasteho; Langui, Dominique; Millecamps, Aymeric; Baron‐Van Evercooren, Anne; Stankoff, Bruno; Lehericy, Stéphane; et al.
Abstract : Inflammation of brain tissue is a complex response of the immune system to the presence of toxic compounds or to cell injury, leading to a cascade of pathological processes that include glial cell activation. Noninvasive MRI markers of glial reactivity would be very useful for in vivo detection and monitoring of inflammation processes in the brain, as well as for evaluating the efficacy of personalized treatments. Due to their specific location in glial cells, myo ‐inositol (mIns) and choline compounds (tCho) seem to be the best candidates for probing glial‐specific intra‐cellular compartments. However, their concentrations quantified using conventional proton MRS are not specific for inflammation. In contrast, it has been recently suggested that mIns intra‐cellular diffusion, measured using diffusion‐weighted MRS (DW‐MRS) in a mouse model of reactive astrocytes, could be a specific marker of astrocytic hypertrophy. In order to evaluate the specificity of both mIns and tCho diffusion to inflammation‐driven glial alterations, we performed DW‐MRS in a volume of interest containing the corpus callosum and surrounding tissue of cuprizone‐fed mice after 6 weeks of intoxication, and evaluated the extent of astrocytic and microglial alterations using immunohistochemistry. Both mIns and tCho apparent diffusion coefficients were significantly elevated in cuprizone‐fed mice compared with control mice, and histologic evaluation confirmed the presence of severe inflammation. Additionally, mIns and tCho diffusion showed, respectively, strong and moderate correlations with histological measures of astrocytic and microglial area fractions, confirming DW‐MRS as a promising tool for specific detection of glial changes under pathological conditions. Abstract : We used diffusion‐weighted MR spectroscopy (DW‐MRS) in the corpus callosum of cuprizone‐fed mice to explore the specificity of myo ‐inositol (mIns) and total choline (tCho) diffusion to glial alterations. Both mIns and tCho apparent diffusion coefficients were significantly elevated in cuprizone versus control mice, likely due to inflammation‐driven glial cell hypertrophy, while histologic evaluation confirmed the presence of severe astrocytic and microglial reactivity. Our study confirmed DW‐MRS as a promising tool for the specific detection of glial changes under pathological conditions.